A Map Joint Estimation of Cfo and Channel in MIMO-OFDM Full-Duplex Transmissions - Bui, Thi Minh Tu; Nguyen, Duy Nhat Vien; Nguyen, Le Hung (Old Journal, 2017)
This paper studies and develops the joint maximum-a-posteriori (MAP) estimation algorithm of carrier frequency offset (CFO) and block-fading channel responses under the Bayesian approach in full-duplex multiple-input multiple-output (MIMO) orthogonal frequency division multiplexing (OFDM) systems. OFDM transmissions are highly susceptible to carrier frequency offset that also introduces inter-carrier interference (ICI) and gives an irreducible error floor in receiver performance. In the full-duplex wireless system, residual self-interference (SI) after radio-frequency (RF) cancellation stage will act as an additional noise and reduces the operating signal-to-noise ratio (SNR). This paper also provides analytical and numerical results of the proposed estimation accuracy (mean square error - MSE) and bit error rate (BER). The simulation results show that the proposed algorithm can offer good performance (BER of desired signal) and good SI and CFO cancellation over a wide range of SNR and CFO.